Review of Gathering Data Instruments and Methods in Children Research - Elyazgi, Moamar; ., . (International Journal of Engineering and Technology, 2018)
Introduction: It is observed that people of different age groups might have different response to the same situation. Often in researches, involving school children data is collected from a guardian rather than from children. Traditional data collection methods like focus group, questionnaires, interviews and observations sometimes have been found to be ineffective with children and hence researchers are compelled to collect data from alternative sources. Conversely, studies have reported that children too have strong opinions and it could be different from their guardianâ€™s. Hence, the purpose of this research is to critically review previous literatureÂ regarding focus group method comparing with other methods that used in conducting research with children with particular emphasis on children studies. Methodology: Current and archival data from research papers have been analysed in this study. Findings: The study reports that the practical considerations and the time it takes to conduct focus group research may discourage many from attempting to collect data using this method. Contribution: This study recommends that adequate effort should be put in place to design suitable instruments to conduct research with children that is devoid of most of the shortcoming found in earlier studies.Â Â